Design and characterization of embedded microheater on CMOS-MEMS resonator for application in mass-sensitive gas sensors - Ahmed, A.Y. (IEEE Computer Society, 2014)
In utilizing CMOS-MEMS resonators as mass-sensitive platforms, a uniform temperature distribution on the membrane surface is critical. In this paper, a novel design of CMOS-MEMS resonator with embedded microheater to control the temperature over the sensing layer was successfully designed and characterized. The CMOS-MEMS resonator was fabricated using 0.35 Î¼m CMOS and post-CMOS micromachining process. Temperature coefficient of resistance (TCR) of aluminum temperature sensor embedded in the membrane was determined by measurement of resistance variation as a function of temperature from 27Â°C and 150Â°C. The TCR of the temperature sensor is found to be 0.00386 and 0.00379 for measurements carried out while temperature is increasing and decreasing, respectively. The total resistance of the temperature sensor and the wire interconnects was theoretically determined to be 74.23 Î© and 94.82 Î©, respectively, making a total resistance of 169.05 Î© when measurements are made through the pads. On the other hand the measured resistance at 27Â°C is found to be 169.06 Î© which is in very good agreement with a difference of 0.006 . The experimental results and analytical values of resistance of the temperature sensor as a function of temperatures shows a good agreement (1.07). TCR of Al is found to 0.00382 with percentage difference of about 2.05 from standard value (39 Ã10-4 C -1). Â© 2014 IEEE.